2006
DOI: 10.1007/s00330-006-0457-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose intranasal versus oral midazolam for routine body MRI of claustrophobic patients

Abstract: The purpose of this study was to assess prospectively the potential of low-dose intranasal midazolam compared to oral midazolam in claustrophobic patients undergoing routine body magnetic resonance imaging (MRI). Seventytwo adult claustrophobic patients referred for body MRI were randomly assigned to one of two treatment groups (TG1 and TG2). The 36 patients of TG1 received 7.5 mg midazolam orally 15 min before MRI, whereas the 36 patients of TG2 received one (or, if necessary, two) pumps of a midazolam nasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
(34 reference statements)
0
20
0
1
Order By: Relevance
“…In our multicenter trial one of the formulations of the used midazolam sprays (ie, the multidose nasal spray) was similar to that used in the recent study of Tschirch et al (5). Two possible limitations of this multidose spray are, first, that administration of the spray has to be performed with the patient in an upright position, and second, this formulation is associated with a relatively high frequency of a temporary burning sensation after application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our multicenter trial one of the formulations of the used midazolam sprays (ie, the multidose nasal spray) was similar to that used in the recent study of Tschirch et al (5). Two possible limitations of this multidose spray are, first, that administration of the spray has to be performed with the patient in an upright position, and second, this formulation is associated with a relatively high frequency of a temporary burning sensation after application.…”
Section: Discussionmentioning
confidence: 99%
“…We only used a VAS to quantify the severity of claustrophobia before and after MRI, and no psychometric test was made such as the Spielberger State-Trait Anxiety Inventory (STAI). However, other investigators also worked successfully using only the VAS (5,10). On the other hand, Hollenhorst et al (2) found similar results using both STAI and VAS, whereas Dantendorfer et al (11) could not find a correlation between values of STAI and the presence of motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our institution's current protocol is adequate and may be recommended to other MR examination centres and institutions. Future studies may investigate the route of midazolam administered (Tschirch FT, 2007) and may also consider a standard dose to assist inpatient studies where anxiety is anticipated.…”
Section: Tiongmentioning
confidence: 99%